Performance of horizontal light pipe for daylighting in high-rise office building in tropical region - Heng, Christopher Yii Sern (2017)
Deep open-plan design is common in high-rise office building due to economic profits. Daylight, which has benefits for energy conservation and both human physiology and psychology; however, is unable to reach the deep area of the office through side windows causing the dependency on electrical lighting. Therefore, this study discourses the usage of light distribution systems, particularly light pipe (LP), to provide illumination in a deep open-plan office in tropical climate. It also focuses on south-facing facade which is the most potential orientation for LP due to the sun position of Johor Bahru that is above the Equator line (latitude of 1o 3’ N and longitude of 103o 37’ E). Most of the previous research was done in temperate climate where the sun position is different from tropical region and focuses on the collector and extractor of LP. The emphasis of this research is on the daylighting performance of the various shapes of transporter and numbers of opening. Nine (9) LP transporters with different numbers of side and a base case were assessed using computer simulation software, Integrated Environment Solution: Virtual Environment (IESVE) that was validated with physical scaled model experiment. Simulations were carried out under overcast sky and intermediate sky with sun condition. The results showed that all the LP cases improve the daylighting performance of an empty open-plan office room. Semi-circle transporter with two openings, which has 14% lesser surface area than a typical rectangular transporter, shows the best performance both quantitatively and qualitatively. This helps to save cost in terms of material usage and creates additional spaces for wiring and ducting in the plenum. This study also concluded that the shape of LP transporter affects the efficiency of LP while the influence of the number of polygon sides and height of the sides without altering the overall height of the transporter are not significant. Thus, the findings of this study promote the usage of LP in deep open-plan high-rise office buildings by proposing design recommendations and guides for building designers.